Philosophy and the land ethic - Rolston, Holmes, 1932-2025, author; Department of Philosophy, Orgeon State University, publisher (Colorado State University. Libraries, 1998)
Environmental ethics was unknown in philosophy until the 1970's, but that was to change rapidly. Dozens of anthologies and systematic works have been published, thousands of articles, and courses are taught in several hundred universities. The land ethic launched by Aldo Leopold insists that moral concern for conserving nature go beyond saving natural resources to a respect for the community of life, respect for intrinsic values in nature, even an Earth ethic for the planetary biosphere. Somewhat ironically, in a century when humans thought they were moving further and further from nature, the natural world has emerged as a focus of moral concern.